Enhancement of Concentration and Mathematics Learning Outcomes Using Discovery Learning Method on Transformation Topic - Sri Rochani (Indonesian Journal of Mathematics Education, 2019)
This study aims to examine whether the actions of educators in using discovery learning models can improve concentration and mathematics learning outcomes in the material of transformation in class IX D of one of the junior high schools in Magelang. This research is a participant class action research. While the models used are the Stephen Kemmis and Robin McTaggart Model. The subjects of this study were students of class IX D of one of the junior high schools in Magelang in the academic year 2018/2019. This research consists of two cycles, namely cycle 1 and cycle 2. The material provided in this study is a transformation topic that includes translation, reflection, rotation, and dilation. Data on the concentration of mathematics learning are obtained using observation sheets. Data on mathematics learning outcomes were obtained using a theory test sheet. The data obtained were analyzed quantitatively and qualitatively. The results of the study show that: (1) learning using discovery learning  models can increase student learning concentration; (2) learning using discovery learning models can improve student learning outcomes; and (3) learning using discovery learning models can increase the concentration of learning and the learning outcomes of IX D students of junior high school.